The Public Space Management Strategy at the Bali Arts Centre during the Annual Bali Arts Festival - I Gusti Ayu Agung Mas Triadnyani; Lily Tjahjandari; Turita Indah Setyani (Pusat Kajian Bali Universitas Udayana, 2024)
The Bali Arts Festival, locally known as Pesta Kesenian Bali (PKB), is an annual colossal festival of performing arts intended to preserve and explore cultural arts, as can be observed from the variety of programs performed, the number of artists involved and the number of viewers. This study analyzes how the public space at the Bali Arts Centre is managed not only to perform a professional and high-quality festival but also to make artists, entrepreneurs and viewers feel comfortable in enjoying it. The data were obtained through interviews, library research, and observation of the 2023 PKB and analyzed using the theory of public space proposed by Gottdiener and Lefebvre. The study concludes that the government has realized that improving the public space and the Arts Centre supporting facilities proves that public space management is as important as the arts curatorial process to present the quality of the PKB and public viewing experiences.